Facile Synthesis of a 3D Nanoarchitectured Li4Ti5O12 Electrode for Ultrafast Energy Storage - Zhao, B.; Deng, X.; Ran, R.; Liu, M.; Shao, Zongping (2015)
Despite enormous efforts devoted to the development of high-performance batteries, the obtainable energy and power density, durability, and affordability of the existing batteries are still inadequate for many applications. Here, a self-standing nanostructured electrode with ultrafast cycling capability is reported by in situ tailoring Li4Ti5O12 nanocrystals into a 3D carbon current collector (derived from filter paper) through a facile wet chemical process involving adsorption of titanium source, boiling treatment, and subsequent chemical lithiation. This 3D architectural electrode is charged/discharged to ≈60% of the theoretical capacity of Li4Ti5O12 in ≈21 s at 100 C rate (17 500 mA g−1 ), which also shows stable cycling performance for 1000 cycles at a cycling rate of 50 C. Additionally, modified 3D carbon current collector with much smaller pores and finer fiber diameters are further used, which significantly improve the specific capacity based on the weight of the entire electrode. These novel electrodes are promising for high-power applications such as electric vehicles and smart grids. This unique electrode architecture also simplifies the electrode fabrication process and significantly enhances current collection efficiency (especially at high rate). Further, the conceptual electrode design is applicable to other oxide electrode materials for high-performance batteries, fuel cells, and supercapacitors.